The behaviour of a wintering flock of Mute Swans Cygnus olor in southern Ireland - Keane, Elizabeth M; O’Halloran, John (Wildfowl, 1992)
The behaviour of a wintering urban flock of Mute Swans was studied over a single winter 1990-91. Daily and weekly activity patterns were monitored. Swimming was the most common activity representing 55% of the time, with feeding and preening being 36% and 15% respectively. The most common feeding strategies were bread feeding, surface feeding and feeding with neck submerged. Patterns of daily activity differed from those of other published studies, feeding increased significantly throughout the day, but the rate of feeding over the study period did not vary. When data for Saturdays and Sundays were omitted (the time of most bread provisioning), a different pattern of bread feeding by swans was observed.